The factors that influence unemployment among graduates / Nur Shafikah Rozani - Rozani, Nur Shafikah (Faculty of Business and Management, 2018)
The purpose of this study is to investigate the factors that influence unemployment among graduates. This is a quantitative research which had used the self-administered electronic questionnaire as the instrument for the collection of data. The data was collected at a percentage of 67.12% out of 73 respondents which was derived from the total population of 93. The respondents are HR Practitioners, top management and manager from companies under Teraju program. Sample selection was based on simple random sampling method. The data collected was the evaluated by using Statistical Package for the Social Science (SPSS). Using SPSS, numerous tests were converged such as reliability analysis, frequency distribution, descriptive analysis, Pearson’s correlation analysis and multiple regression. Based on the findings obtain from descriptive analysis on the demographic, it shows that the female are the highest respondent than male that contribute in this study. Data findings from Pearson Correlation analysis shows the result indicated that the factors which include lack of English proficiency, lack of employability and qualification mismatch are related to unemployment among graduates. Based on the multiple regression analysis, the most influences element in unemployment among graduates is lack of English proficiency with the highest Beta Value is 0.338.